Smoking among Brazilian adolescents during the COVID-19 pandemic: a cross-sectional study - Malta, Deborah Carvalho; Gomes, Crizian Saar; Vasconcelos, Nádia Machado de; Alves, Francielle Thalita Almeida; Ferreira, Arthur Pate de Souza; Barros, Marilisa Berti de Azevedo; Lima, Margareth Guimarães; Szwarcwald, Celia Landmann (São Paulo Medical Journal, 2023)
BACKGROUND: The social distancing measures during the coronavirus disease 2019 (COVID-19) pandemic resulted in mental suffering among adolescents, leading to risky consumption of psychoactive substances such as tobacco. OBJECTIVE: To analyze the factors associated with tobacco use among adolescents during the COVID-19 social distancing period in Brazil. DESIGN AND SETTING: Cross-sectional study used data from ConVid Adolescentes survey in Brazil. METHODS: Tobacco use was assessed before and during social distancing. The explanatory variables investigated were sex, age, race/skin color, type of school, maternal education, region of residence, adherence to social restriction measures, number of close friends, sleep quality during the pandemic, mood, passive smoking, use of alcoholic beverages during the pandemic, sedentary behavior, and physical activity. A logistic regression model was used for the data analysis. RESULTS: Tobacco use by adolescents did not change during the pandemic (from 2.58% to 2.41%). There was a higher chance of tobacco use among adolescents aged between 16 and 17 years, self-reported black ones, residing in the South and Southeast regions, reported feeling sad and loneliness, had sleeping problems that worsened, were using alcoholic beverages during the pandemic, and were passive smokers at home. Adolescents whose mothers had completed high school or higher, had strict social restrictions, and increased their physical activity during the pandemic had a lower chance of tobacco use. CONCLUSION: Tobacco uses during the COVID-19 pandemic was higher in vulnerable groups, such as black adolescents and those with mental suffering.